2013
DOI: 10.1002/bmb.20684
|View full text |Cite
|
Sign up to set email alerts
|

The use of an active learning approach to teach metabolism to students of nutrition and dietetics

Abstract: This article describes the transition from a traditional instructor-centered course, based on lectures, to a studentcentered course based on active learning methodologies as part of the reform of the Spanish higher education system within the European Higher Education Area (EHEA). Specifically, we describe the use of active learning methodologies to teach metabolism to students of nutrition and dietetics during the first year of their professional training in a 4-year undergraduate degree (Bachelor of Human Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
2
12
0
5
Order By: Relevance
“…Our findings that fellows preferred this method of active learning over a more traditional lecture-based format support what has been previously reported in the literature for residents 10,11,15,16. We are unaware of studies showing the practical benefits of an active learning curriculum in a specialty fellowship training program.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Our findings that fellows preferred this method of active learning over a more traditional lecture-based format support what has been previously reported in the literature for residents 10,11,15,16. We are unaware of studies showing the practical benefits of an active learning curriculum in a specialty fellowship training program.…”
Section: Resultssupporting
confidence: 84%
“…Active learning requires students to be part of the discussion and to analyze, synthesize, and evaluate information and attempt to solve problems 1012. When students in active learning sessions begin to explore topics off target, it is the responsibility of the facilitator to bring them back to the main objectives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case‐based learning is a problem‐based pedagogy in nutrition education. Previous studies have found that students who learn through case‐based learning had higher course pass rates than instructor‐centred teaching; in addition, students in case‐based learning had positive attitudes and did not perceive an extra workload (Gonzalez‐Sancho et al, ). However, the application of case‐based learning has been criticized as a high‐risk educational strategy.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, a few courses for nutrition and dietetics majors have used active learning—in particular, PBL and TBL—to introduce topics such as metabolism , solve problems in food science , and improve learner autonomy . At the Universidad Autónoma de Madrid, first year undergraduate nutrition and dietetics students used an approach incorporating elements of PBL and TBL—including problems and case studies workshops, discussion workshops, self‐assessment and unit quizzes, and tutorials—in place of lecture to learn about metabolism.…”
Section: Introduction/backgroundmentioning
confidence: 99%